Painful keratocystic odontogenic tumor due to secondary infection associated to pulp necrosis - Klein, Isadora Peres; Martins, Manoela Domingues; Martins, Marco Antonio Trevizani; Sant'Ana Filho, Manoel; Rados, Pantelis Varvaki; Carrard, Vinicius Coelho (Journal of Oral Diagnosis, 2016)
The keratocystic odontogenic tumor (KCOT) is defined as a benign, odontogenic, uni- or multicystic intraosseous tumor with infiltrative behavior. KCOTs occur over a broad age range, predominantly in the second and third decades of life.This odontogenic tumor is usually asymptomatic and diagnosed incidentally on routine radiographs. Growth is typically medullary and there is no bone expansion in the majority of cases. In the present case, the patient exhibited pain and expansion of buccal cortical bone, unusual findings in this tumor.This could be related to pulp necrosis of the adjacent decayed tooth, leading to a secondary infection of the KCOT.These circumstances become the diagnosis difficult, because the clinical signals and symptoms strongly mimic an inflammatory lesion.